2012
DOI: 10.1080/00038628.2012.702449
|View full text |Cite
|
Sign up to set email alerts
|

Post-occupancy evaluation and experimental feedback of a net zero-energy building in a tropical climate

Abstract: Located in the French tropical Island of La Reunion in the Indian Ocean, the ENERPOS building was inaugurated in January 2009. The building is located in the Saint Pierre Campus of the University of Reunion Island. It was designed to be a net zeroenergy building with mixed-mode air-conditioning systems in some areas (natural ventilation, ceiling fans, air conditioning) and efficient passive solutions sets usually used in tropical areas -i.e. efficient solar protection coupled with cross natural ventilation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…A post-occupancy evaluation assessed the perception of students and staff of a zero-energy building, located in a French island in the Indian Ocean (tropical climate) [223]. The building was designed to be mixedmode in some areas and uses passive strategies.…”
Section: Thermal Comfort In Universitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A post-occupancy evaluation assessed the perception of students and staff of a zero-energy building, located in a French island in the Indian Ocean (tropical climate) [223]. The building was designed to be mixedmode in some areas and uses passive strategies.…”
Section: Thermal Comfort In Universitiesmentioning
confidence: 99%
“…The building was designed to be mixedmode in some areas and uses passive strategies. Results indicate that during most of the year, users are in thermal comfort without using air-conditioning [223]. Serghides et al [224] identified the inappropriate use of cooling and heating systems (very low temperatures in summer and very high temperatures in winter) in a university building in Cyprus.…”
Section: Thermal Comfort In Universitiesmentioning
confidence: 99%
“…Since different nZEB solutions are needed for different climate zones, many researchers have also studied how nZEBs can be achieved in different climate zones and regions [32][33][34][35][36][37][38]. Such studies are intended to provide guidelines and optimal solutions that shall help designers, in the studied climate zones, to make decisions during their design process to achieve nZEBs.…”
Section: Methodologies and Recommendationsmentioning
confidence: 99%
“…BIPVs use the building envelope to incorporate solar cells, which convert sunlight directly into electricity. Such installations are not only the ultimate showcase for this clean, renewable energy generation technology, but they also represent a perfect application of on-site energy production (Lenoir, Baird, and Garde 2012). Various studies have reported on the performance, optimization and economic viability of these systems (Bakos, Soursos, and Tsagas 2003;Cook and Sproul 2011;Li et al 2012;Zogou and Stapountzis 2011) as well as on the applicability of hybrid solar PV and thermal systems (Chow 2010;Kumar and Rosen 2011;Tiwari, Mishra, and Solanki 2011).…”
Section: Literature Reviewmentioning
confidence: 99%